Usborne psychology for beginners - Bryan, Lara (Beginners series, 2022)
"An accessible introduction to psychology for complete novices. Fully-illustrated and filled with real-world examples, this book explains the basics of psychology, from how people think, feel and behave to how scientists can study and be sure about what is actually going on in other people's brains."